2021
DOI: 10.1080/0886022x.2021.1977319
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-albumin ratio: a risk factor associated with technique failure and mortality in peritoneal dialysis patients

Abstract: Background Peritoneal dialysis (PD) patients have a high incidence of poor clinical outcomes, which is related to the inflammatory and nutritional status of this population. Platelet-to-albumin ratio (PAR), recently identified as a useful biomarker to monitor inflammation and nutrition, can predict a poor prognosis in various diseases. The aim of this study was to investigate the association between PAR and technique failure and mortality in PD patients. Methods This si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…PAR was also illustrated to predict the mortality of patients suffering from severe fever with thrombocytopenia syndrome ( 17 ). PAR plays a similar role in predicting outcomes of patients with peritoneal dialysis ( 18 ). Hence, the consistent results of multiple articles suggested that the PAR might become a novel prognostic indicator in the future ( 4 , 5 , 16 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAR was also illustrated to predict the mortality of patients suffering from severe fever with thrombocytopenia syndrome ( 17 ). PAR plays a similar role in predicting outcomes of patients with peritoneal dialysis ( 18 ). Hence, the consistent results of multiple articles suggested that the PAR might become a novel prognostic indicator in the future ( 4 , 5 , 16 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…PAR plays a similar role in predicting outcomes of patients with peritoneal dialysis ( 18 ). Hence, the consistent results of multiple articles suggested that the PAR might become a novel prognostic indicator in the future ( 4 , 5 , 16 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical investigations have gained insight into the prognostic value of PAR. Yang et al [ 20 ] performed a single-center study with 405 peritoneal dialysis patients and reported that PAR was a risk factor associated with mortality. Moreover, PAR not only contributed to critical illness but was also implicated in the risk assessment of a list of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…13 Relationships between platelet ratio and chronic obstructive pulmonary disease, acute aortic dissection, peritoneal dialysis, haemodialysis, and severe pneumonia have been reported in numerous studies. [14][15][16][17][18] Decreased platelet count in severe disease is a predictor of mortality. 19 This suggests that platelet ratio may be used as a tool for predicting the prognosis of patients with AMI.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%